2000
DOI: 10.1094/cchem.2000.77.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying and Foaming Properties of Gluten Hydrolysates with an Increasing Degree of Hydrolysis: Role of Soluble and Insoluble Fractions

Abstract: Cereal Chem. 77(4): [414][415][416][417][418][419][420] Gluten solubility was improved by enzymatic proteolysis at moderate acidic pH level. Reversed-phase HPLC analysis of gluten hydrolysates with a degree of hydrolysis (DH) in the range of 0-5% showed that both hydrophilic and hydrophobic soluble peptides were released. Emulsifying and foaming properties of hydrolysate dispersions at 3.75 mg/mL decreased with the increasing DH at all pH levels and salt conditions investigated.On the other hand, the soluble f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 21 publications
6
32
0
Order By: Relevance
“…The maximum value (56%) was obtained for 0.4 M. Initially, soybean had a reduction in the FS from 22 to 20% from 0.0 to 0.2 M, but at 0.4 M it began to increase reaching a maximum value of 40% for a 0.8 M salt solution. These results are similar to those of previous studies, in which foam stability increases with the addition of salts (WU et al, 2009;LINARES et al, 2000). Furthermore, Akintayo et al (1999) found a measure of the influence of ionic strength on the foam properties on Cajanus cajan concentrates.…”
Section: Oil and Water Absorption Capacitysupporting
confidence: 91%
“…The maximum value (56%) was obtained for 0.4 M. Initially, soybean had a reduction in the FS from 22 to 20% from 0.0 to 0.2 M, but at 0.4 M it began to increase reaching a maximum value of 40% for a 0.8 M salt solution. These results are similar to those of previous studies, in which foam stability increases with the addition of salts (WU et al, 2009;LINARES et al, 2000). Furthermore, Akintayo et al (1999) found a measure of the influence of ionic strength on the foam properties on Cajanus cajan concentrates.…”
Section: Oil and Water Absorption Capacitysupporting
confidence: 91%
“…This indicates that lipophilized peptides are preferentially adsorbed at the air/water interface where they form a stable film, whereas native peptides remain in the aqueous solution without participating in foam formation. An equivalent observation has been made in emulsions where only the most hydrophobic peptides contribute to the surface phenomenon (2,19,20). Thus, acylation of the amino groups of small peptides results in amphiphilic compounds that are surface-active.…”
Section: Peptides Adsorbed At the Air/water Interfacementioning
confidence: 84%
“…Additionally, the balance of hydrophilic and hydrophobic forces of peptides is also mentioned as an important cause of solubility enhancement (Kristinsson and Rasco, 2000;Gbogouri et al, 2004). Several reported studies have also confirmed that increasing DH increases solubility of protein hydrolysates (Quaglia and Orban, 1987;Chobert et al, 1988a, b;Mutilangi et al, 1996;Linar es et al, 2000;Gbogouri et al, 2004;Klompong et al, 2007;Souissi et al, 2007;Balti et al, 2010;Geirsdottir et al, 2011). The solubility of the hydrolysates is especially improved at the proteins isoelectric point, pI (Chobert et al, 1988b).…”
Section: Solubilitymentioning
confidence: 95%
“…Foam capacity of proteins can be improved by making them more flexible (hydrolysis) and exposing more hydrophobic residues for the adsorption at the air-water interface (Multilangi et al, 1996). Several studies showed decreased foaming stability for protein hydrolysates compared to that of the untreated proteins (Linar es et al, 2000;Klompong et al, 2007;Souissi et al, 2007;Mune, 2015;Zou et al, 2016). Some studies, on the other hand, reported increased foaming capacity of hydrolysates compared to untreated proteins (Kuehler and Stine, 1974;Balti et al, 2010;Mune 2015).…”
Section: Foaming Propertiesmentioning
confidence: 99%